Oxygen isotope speedometry in granulite facies garnet recording fluid/melt-rock interaction (Sør Rondane Mountains, East Antarctica) - Higashino, Fumiko; Rubatto, Daniela; Kawakami, Tetsuo; Bouvier, Anne-Sophie; Baumgartner, Lukas P. (Journal of Metamorphic Geology, 2019)
In situ analysis of a garnet porphyroblast from a granulite facies gneiss from Sør Rondane Mountains, East Antarctica, reveals discontinuous step‐wise zoning in phosphorus and large δ18O variations from the phosphorus‐rich core to the phosphorus‐ poor rim. The gradually decreasing profile of oxygen isotope from the core (δ18O = ~15‰) to the rim (δ18O = ~11‰) suggests that the 18O/16O zoning was originally step‐wise, and modified by diffusion after the garnet rim formation at ~800°C and 0.8 GPa. Fitting of the 18O/16O data to the diffusion equation constrains a duration of the high‐T event (~800°C) to c. 0.5–40 Ma after the garnet rim formation. The low δ18O value of the garnet rim, together with the previously reported low δ18O values in metacarbonates, indicates regional infiltration, probably along a detachment fault, of low δ18O fluid/melt possibly derived from meta‐mafic to ultramafic rocks.